FLOUTING MAXIMS IN WHITE HOUSE DOWN - Rebekka Sinaga (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2020)
Cooperative principles theorized by Grice (1975) explaines the way people use the language well and efficiently. There are four maxims in order to achieve connection during conversation, i.e. the maxims of quality, quantity, relation, and manner. However, people do not always follow and obey the Cooperative principle and instead flout maxim. The aim of this research was to discuss about the types of maxim which were flouted in the movie White House Down written by James Vand Erbilt. As a result, the researcher found 15 samples of flouted maxim, maxim of quantity 4 data, maxim of quality 2 data, maxim of manner 5 data, and 4 data maxim of relation.